Capturing the Role of Context in Complex System Change: An Application of the Canadian Context and Capabilities for Integrating Care (CCIC) Framework to an Integrated Care Organisation in the UK - Sheena Asthana; Felix Gradinger; Julian Elston; Susan Martin; Richard Byng (International Journal of Integrated Care, 2020)
Introduction: If integrated care approaches are to be properly adapted to local contexts, a better understanding is required of key determinants of implementation and how these might be appropriately supported. Purpose: This study applied the Canadian Context and Capabilities for Integrating Care (CCIC) Framework to investigate factors influencing the implementation and outcomes of a complex integrated care change programme in Torbay and South Devon (TSD) and, more specifically, in one of five sub-localities, Coastal. Methods: A case study method using embedded ‘Researchers in Residence’ to conduct action-based participatory research and deploying mixed qualitative methods. Results: The relative importance of some domains differ between the English and Canadian studies. In this case study, physical features (structural and geographic) were found to be very pertinent to the relative success of the Coastal Locality, as were empowered clinical leadership, with readiness for change being expressed through processes and cultures that were risk-enabling, strengths-based, person-/outcome-focused. Conclusions: The CCIC Framework provided a useful tool capturing key elements of complex system change with key domains being transferable across settings, while also finding local variation in the UK. This would encourage its wider application so that further comparisons can be made of the ways in which different contextual and implementation properties impact upon delivery and outcomes.